Media Pembelajaran Pada Abad XV M (Studi Kasus Prasasti Widodaren, Gerba, dan Pasrujambe) - Rakai Hino Galeswangi (Berkala Arkeologi, 2020)
This study was aimed at analyzing and interpreting the instructional media existing in the classical period of the Hindu - Buddhist kingdoms. The object of the study was inscriptions found on the Semeru Slope, inclduing Widodaren, Pasrujambe, and Gerba. This study employed a qualitative method with an archeological-historical framework. The data was collected through a literature review and in-situ research of the inscriptions. The collected data was analyzed using a structural analysis in the forms of transliteration of the contents and meaning written at the inscriptions. The study found that there is evidence of the use of instructional media in teaching process. This finding is also supported by the Nāgarakṛtâgama and Bujaņga Manik manuscripts which narrate educational and moral values as one of the characteristics of instructional media. In addition, the instructional media serve as a tool support the teaching and learning process at that time.